SISTEM INFORMASI PENJUALAN DAN PEMBELIAN OBAT PADA APOTEK BERBASIS WEB(STUDI KASUS: APOTEK ANAYA PLAJU) - Rika Tri Diana; Tata Sutabri (CV. ADIBA AISHA AMIRA, 2023)
Information systems are an important part of managing and carrying out all activities. One of them is the drug sales and purchase information system, the drug sales and purchase information system currently used at Anaya Plaju Pharmacy still does not use a computer-based information system. In meeting the needs of pharmacies, especially to deal with the problem of selling and buying drugs, making reports, sales and purchasing systems have not run optimally as expected so pharmacies still need a better system using a computerized system. The methodology used is web-based. Web-based drug sales and purchase information system is an application developed to assist the process of selling and buying drugs at a pharmacy. This application is designed using web and database technology so that it can be accessed via the internet easily. The features provided in this system include drug stock management, customer data management, purchases, sales, and sales reports. With this system, it is hoped that the transaction process at the pharmacy can become more efficient and organized, so as to improve service quality and customer satisfaction. In addition, a web-based drug sales and purchase information system can also assist pharmacies in managing drug inventory more effectively and efficiently